Investigation of cutting conditions on tool life in shoulder milling of Ti6Al4V using PVD coated micro-grain carbide insert based on design of experiments. Issue 6 (June 2020) - Tatar, Kourosh; Sjöberg, Sören; Andersson, Niklas
Abstract: Tool life prediction is generally of great importance in all metal cutting processes, including milling titanium. In this paper, tool life testing was performed based on full factorial design. The cutting speed and width varied between 100 and 120 m/min, and 10 and 70 percent of tool diameter, respectively. All cutting tests were performed in Ti6Al4V under wet conditions using Physical Vapor Deposition (PVD) coated milling inserts. The wear limit was set to 0.2 mm. The data were analyzed using multiple regression analyses, where the method of least squares was applied. A mathematical tool life model was established. Roughly, for each one percent increase in cutting width, tool life decreases on average by one percent, and an increase in cutting speed by a percent leads to a decrease in tool life by four percent. The adequacy of the model was verified using analysis of variance at 95% confidence level. Tool life contour in cutting width and speed was generated from the model. The results can be used for selecting optimum cutting parameters for providing a desired tool life or maximum metal removal rates for a favored tool life. Abstract : Materials Science; Mechanical Engineering; Tribology; Machining; Coatings; Metals; Materials Application; Materials Processing; Tool life; Milling; PVD coating; Ti6Al4V; Design of experiments.